PENGARUH RETURN ON ASSET, EARNING PER SHARE, ECONOMIC VALUE ADDED, DAN PRICE TO BOOK VALUE TERHADAP RETURN SAHAM - Prakoso, Bayu; Puspawati, Dewita (Prosiding University Research Colloquium, 2021)
The high increase in the population that is increasing, of course,really needs a lot of places to live, housing development, buildings,shopping centers, and others, especially in the property sector, soproperty and real estate companies are always the first sight by thecommunity because they provide their needs community board.However, not all companies will distribute the returns they expect. The purpose of this study was to determine the effect of Return onAssets, Earning Per Share, Economic Value Added, and Price toBook Value on stock returns. The population of this study areproperty and real estate companies listed on the Indonesia StockExchange for the period 2016-2019. The sample in the studyamounted to 132 with the sampling technique using purposivesampling method. The method of analysis uses multiple linearregression analysis techniques. The results showed that earningsper share and economic value added had an effect on stock returns,while return on assets and price to book value had no effect on stockreturns.